Informing the Future : Critical Issues in Health. (National Academies Press, Ebsco Publishing [distributor], 2003)
The Institute of Medicine: Adviser to the Nation -- Highlighted reports -- Global health and infectious disease -- Health sciences and the research enterprise -- Ensuring food safety and proper nutrition -- Assuring the public's health -- Health care delivery system and performance capabilities -- Human security and bioterrorism -- Military personnel and veterans -- Robert Wood Johnson Health Policy Fellowships Program -- Senior nurse scholar program -- Recent and upcoming reports.